The sense of the human fate in the anatelic philosophy - Zachariasz, Andrzej L. (Folia Philosophica, 2000)
The notion of fate is ambiguous. In various cultures it is associated with various interpretations.As a rule, the fate is often identified with what influences the course of man’s life but is beyond his control. The human fate is also the experience of being. Philosophy provides a possibility of reflecting on the experience of the experience of being perceived in this way. In each case a philosophical interpretation of fate will be an attempt at understanding the human mode of existence. Reflecting on fate, we have first to notice that man as an individual being always finds himself in some kind of situation. At the same time, as a being man unites within himself some activity related to the surrounding world and a possibility of its realisation. As an active being he is first of all a thinking being, that is he consciously pursues his activity. It is consciousness then that determines in the first place man’s mode of existence in the world. This means also that, being faced with particular events, he can assume an active or a passive attitude. In other words, he can either submit to his fate, or he can undertake actions aimed at changing the course of events. One of the theoretical propositions concerning man’s position towards his fate is the anatelic thinking, that is a kind of thinking which is geared on going beyond one's limitations, and one the creation of one’s self. It is assumed here that, regardless of whether tha fate favours such self-creation or not, the sense of any activity consists in creating the conditions in which the realisation of a conscious existence, and, by the same token, a full existence of man as consciousness, becomes possible.